Analyzing the Issues in the Implementation of Authentic Assessment in the 2013 Curriculum - Hidayati, Abna; Bentri, Alwen; Rahmi, Ulfia (AT-TALIM, 2017)
The  implemention of authentic assessment  in the   2013 Ccurriculum  has been encountered by various challenges. Teacher have to use numerious instruments, which made them quite which are regarded more complicated. this study focused on the analysis of issues experienced by teachers in implementingng theauthentic assessment within the 2013 curriculum. This study used quantitatif method in which questionnaire was  distributed to the teachers. Population included all teachers in Padang whose schools are applying the 2013 curriculum. 120 teacher were randomly taken as the sample.  The results show that in terms of the affective aspect, the teachers had not yet been optimal in conducting self- and peer assessment for the students, thus the further improvement is seriously recomended. In light of the the cognitive aspect, the teachers had done a very good assessment. They had made a variety of assessment types, especially in the essay and oral tests. However, the assessment of psychomotor aspect was not also optimally done need some improvement. From these results, it is hoped that the teachers can further enhance the assessment procedures of the three criteria for better learning outcomes. The school principals should be able to create opportunities for the teachers to take training in the Applying authentic assessment.